Modelo de optimización en la gestión de inventarios mediante algoritmos genéticos (2011)
This paper presents the design of a genetic algorithm (GA) that optimizes inventory management in supply chains. They were considered warehousing, distribution, and manufacturing product costs, plus the cost of individual items to be ordered. The string used in the simulation contains 5 levels, being: customer, retail, warehouse, distributor and factory. The amounts of each pair were considered to be evaluated by the GA in the best chromosome. Additionally the BMN coefficients model was used to generate the evaluation function of chromosomes selected by the GA and satisfies the constraints considered in the model.